Factores de riesgo físico y salud laboral de los trabajadores del área de perforación y mantenimiento de la empresa petrolera Chuanquing Drilling Engineering Company Limited International LTD - CCDC. Propuesta de un programa de control de riesgos físicos. - Vega, Oswaldo Neptalí (2015)
THE PETROLEUM COMPANY CHUANQING DRILLING ENGINEERING COMPANY LIMITED-CCDC INTERNATIONAL LTD IS A COMPANY THAT DRILLS OIL WELL. It is located in the province of Sucumbios, canton Nueva Loja parish Pacayacu; processes and workstations involving all hazards, order to control these physical hazards assessment was performed by determining the limits of exposure to noise temperaturas, identifying and evaluating the physical hazards the observation which is shown on the hazard map was used. After identified hazards are evaluated through the application of formulas valuing the maximum limits of exposure in workplace. This analysis was identified that exposisiones noise and thermal confor in the process of drilling and maintenance, are beyond the limits of standardsthis brings to alterations in the health of workers, the main factors illness as hearing loss. Assessed the physical hazards are set to light the dangers to health and from here you define prevention and protection to be used. About exposure to noise and temperature a variety of recommendations are made because the work in the area of drilling and maintenance involves first optimize the environmental conditions and thereafter the appropriate analizis hazard. The form of this work corresponds to workable project that is to say bibliographic and field research to achieving after its diagnosis, a proposal for the intervention. The theoretical framework establishes as a fundamental category: workplace health, environmental noise and temperature conditions, the proposal is to a control system.